Factors Influencing Success Rate of Contractors in Competitive Bidding for Construction Works in South-East, Nigeria - Aje, Isaac Olaniyi; Oladinrin, Timo Olugbenga; Nwaole, Angeline Ngozika Chibuike (Penerbit Universiti Sains Malaysia, 2016)
The focal point of this study was to assess the perspectives of construction professionals on factors influencing tender prices of construction works and the contribution of the factors to the success rate of contractors. Using literature review and questionnaire survey, 15 factors were identified in respect to contractors' tender price and success rate in Nigeria. The findings of this study based on the results of statistical analyses (mean score and chi-square) reveal that all the construction professionals (architects, builders, engineers and quantity surveyors) are of the opinion that material availability, labour productivity and level of profit are the most significant factors that highly influence tender price of construction works and consequently affect the success rate of contractors in competitive bidding. Project definition and construction plan have least influence on contractors' tender price. Also, it was found that government policy does not have significant effect on contractors' success rate in competitive bidding in Nigeria. It is hoped that the information presented in this paper will be of interest to all parties concerned, including Nigerian construction companies and foreign companies planning to enter the Nigerian construction market. In addition, while the research focused on a particular country, Nigeria, the study can be replicated in other countries particularly developing countries and the results can be compared.